PENERAPAN SUPERVISI AKADEMIK UNTUK MENINGKATKAN KOMPETENSI GURU DALAM MENYUSUN ADMINISTRASI PENILAIAN DI SD INPRES DAMARBIMA KECAMATAN HEWOKLOANG - SILVESTER NONG MANIS (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
The purpose of this principal’s action research is to improve the pedagogical competence of teachers at Damarbima Inpres Elementary School in preparing the administration of assessment through academic supervision. This type of research used in this research is school action research. The activities in this study consisted of the stages of action planning, action implementation, observation, and reflection. Data collection techniques used class observation techniques. The observation instrument used was a teacher’s ability assessment tool (APKG) in the form of a learning administration assessment Instrument. Analysis of the data used is a comparative descriptive analysis technique. Quantitative data obtained is described in the form of words or explanations. Data comparison is then performed to ensure whether there is an increase in the ability of teachers in the assessment of learning administration. The results showed the findings that academic supervision could improve the ability of teachers in preparing administrative assessment in learning at SD Inpres Damarbima by 26.2%.